The Number of MRGPRX2-Expressing Cells Is Increased in Skin Lesions of Patients With Indolent Systemic Mastocytosis, But Is Not Linked to Symptom Severity - Pyatilova, Polina; Ashry, Tameem; Luo, Yanyan; He, Jiajun; Bonnekoh, Hanna; Jiao, Qingqing; Moñino-Romero, Sherezade; Hu, Man; Scheffel, Jörg; Frischbutter, Stefan; Hermans, Maud A. W.; Youngblood, Bradford A.; et al. (Frontiers in Immunology, 2022)
Background: Recently, expression of the mast cell (MC) receptor Mas-related G protein–coupled receptor X2 (MRGPRX2) has been detected in lesional skin of adult patients with cutaneous mastocytosis. As of yet, little is known about the clinical relevance of MRGPRX2 and its agonists in patients with mastocytosis, including indolent systemic mastocytosis (ISM). Methods: MRGPRX2 and MRGPRX2 agonists, cortistatin (CST) and major basic protein (MBP), were analyzed in lesional and nonlesional skin of patients with ISM and skin of healthy controls by immunohistochemistry. Co-localization of MRGPRX2 and MRGPRX2-mRNA with the MC marker tryptase was assessed by immunofluorescence microscopy and in situ hybridization, respectively. We assessed clinical, demographic and laboratory data, including mastocytosis activity score (MAS), serum tryptase and KIT D816V allele burden. Results: The number of MRGPRX2-expressing (MRGPRX2+) cells, MRGPRX2-mRNA+ MCs, CST-expressing (CST+) and MBP-expressing (MBP+) cells was significantly higher in lesional skin as compared to nonlesional skin and/or skin of healthy controls (all p<0.05). Increased numbers of MRGPRX2+ cells, MRGPRX2-mRNA+ MCs, CST+ and MBP+ cells were not associated with clinical and laboratory features of ISM, including disease burden, symptom severity, evidence of anaphylaxis and tryptase levels. Conclusions: Skin lesions of patients with ISM showed high numbers of MRGPRX2+ cells, although they were not linked to symptom severity. Clinical relevance of the MRGPRX2-mediated pathway of MC activation in ISM remains unclear and should be investigated in further studies.